Prevalence and Evolution of Core Photosystem II Genes in Marine Cyanobacterial Viruses and Their Hosts - Sullivan, Matthew B (Public Library of Science, 2006)
Cyanophages (cyanobacterial viruses) are important agents of horizontal gene transfer among marine cyanobacteria, the numerically dominant photosynthetic organisms in the oceans. Some cyanophage genomes carry and express host-like photosynthesis genes, presumably to augment the host photosynthetic machinery during infection. To study the prevalence and evolutionary dynamics of this phenomenon, 33 cultured cyanophages of known family and host range and viral DNA from field samples were screened for the presence of two core photosystem reaction center genes, psbA and psbD. Combining this expanded dataset with published data for nine other cyanophages, we found that 88% of the phage genomes contain psbA, and 50% contain both psbA and psbD. The psbA gene was found in all myoviruses and Prochlorococcus podoviruses, but could not be amplified from Prochlorococcus siphoviruses or Synechococcus podoviruses. Nearly all of the phages that encoded both psbA and psbD had broad host ranges. We speculate that the presence or absence of psbA in a phage genome may be determined by the length of the latent period of infection. Whether it also carries psbD may reflect constraints on coupling of viral- and host-encoded PsbA–PsbD in the photosynthetic reaction center across divergent hosts. Phylogenetic clustering patterns of these genes from cultured phages suggest that whole genes have been transferred from host to phage in a discrete number of events over the course of evolution (four for psbA, and two for psbD), followed by horizontal and vertical transfer between cyanophages. Clustering patterns of psbA and psbD from Synechococcus cells were inconsistent with other molecular phylogenetic markers, suggesting genetic exchanges involving Synechococcus lineages. Signatures of intragenic recombination, detected within the cyanophage gene pool as well as between hosts and phages in both directions, support this hypothesis. The analysis of cyanophage psbA and psbD genes from field populations revealed significant sequence diversity, much of which is represented in our cultured isolates. Collectively, these findings show that photosynthesis genes are common in cyanophages and that significant genetic exchanges occur from host to phage, phage to host, and within the phage gene pool. This generates genetic diversity among the phage, which serves as a reservoir for their hosts, and in turn influences photosystem evolution.